1991
DOI: 10.5935/0305-7518.19910043
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-laden macro phages in bone marrow of leprosy patients

Abstract: Summary While conducting a study to observe bone marrow cytomorphological changes in multi bacillary leprosy, lipid laden macrophages as seen in sphingolipi doses were noted. The present study was planned to observe the occurrence and morphological characterization of these macrophages in various types of leprosy. Bone marrow records from 48 cases of paucibacillary and 72 cases of multibacill ary leprosy were analysed. The macrophages accounting at the most for 3·5% of marrow cells were observed in 5 cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
0
1
Order By: Relevance
“…The pathogenesis of anaemia in malaria is multifactorial. A complex chain of pathogenetic processes involving mechanical destruction of parasitized RBCs, marrow suppression, ineffective erythropoiesis, and accelerated immune destruction of nonparasitized RBCs have been implicated [11]. Thrombocytopenia was a common observation in falciparum malaria with spontaneous recovery on treatment but in this study, it showed increased thrombocytes.…”
Section: Discussioncontrasting
confidence: 36%
“…The pathogenesis of anaemia in malaria is multifactorial. A complex chain of pathogenetic processes involving mechanical destruction of parasitized RBCs, marrow suppression, ineffective erythropoiesis, and accelerated immune destruction of nonparasitized RBCs have been implicated [11]. Thrombocytopenia was a common observation in falciparum malaria with spontaneous recovery on treatment but in this study, it showed increased thrombocytes.…”
Section: Discussioncontrasting
confidence: 36%